2018
DOI: 10.1177/0030222818755284
|View full text |Cite
|
Sign up to set email alerts
|

The Impact on Mental Health of Losing an Only Child and the Influence of Social Support and Resilience

Abstract: The number of parents who have lost their only child (PLOCs) has increased annually with the implementation of the birth control policy in mainland China. This study aimed to investigate the mental health status of PLOCs and the influence of social support and resilience. Study 1 recruited 100 PLOCs and 88 nonbereaved parents, and compared differences in depression, anxiety, and loneliness. Study 2 investigated the influence of social support and resilience on the mental health of PLOCs via a mediating model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 45 publications
7
63
2
3
Order By: Relevance
“…Different types of social support had different predictive effects on inclusion in a particular profile group. In line with previous findings with other traumatic populations (Dai et al, 2016;Rzeszutek et al, 2017) and following bereavement (Cao et al, 2018;Xu et al, 2017), we found that parents who perceived lower levels of support from family and significant others were more likely to be included in the profile group with higher levels of PTSD and depressive symptoms. According to the theory of social support, the more social support a person has, the better the individual can cope with various challenges from the outside world (Cao et al, 2018;Van Der Houwen et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Different types of social support had different predictive effects on inclusion in a particular profile group. In line with previous findings with other traumatic populations (Dai et al, 2016;Rzeszutek et al, 2017) and following bereavement (Cao et al, 2018;Xu et al, 2017), we found that parents who perceived lower levels of support from family and significant others were more likely to be included in the profile group with higher levels of PTSD and depressive symptoms. According to the theory of social support, the more social support a person has, the better the individual can cope with various challenges from the outside world (Cao et al, 2018;Van Der Houwen et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Social support is individuals' perception or experience in terms of being involved in a social group where people mutually support each other (Cao et al, 2018). Family, friends or any other important relatives could provide material and spiritual support, which probe to be positively associated with mental health (Rothon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, shidu parents are not only afflicted by child loss but also suffer from identity loss and social stigmatization ( Zheng and Lawson, 2015 ). Compared to Chinese parents with a living child or who had given birth again, they had a higher risk of intense grief, depression, anxiety, posttraumatic stress, and chronic diseases ( Xu et al, 2014 ; Zheng et al, 2017 ; Cao et al, 2018 ; Yin et al, 2018 ). Additionally, compared with a prevalence of PGD of about 10% in general bereaved people ( Lundorff et al, 2017 ), the prevalence rate in shidu parents was 35.5% ( Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the loss of the only child often results in interpersonal loss. Additionally, because of Chinese traditional filial piety culture, adult children are the main care providers, giving emotional and financial support to their parents ( Zheng et al, 2017 ; Cao et al, 2018 ). Therefore, losing the only child also leads to economic losses, especially in rural areas ( Liang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%